Analisis Kesalahan Siswa dalam Menyelesaikan Masalah Matematika Berdasarkan Teori Kastolan - Nida Sri Rahmita Hasibuan; Yenita Roza; Maimunah Maimunah (Universitas Pendidikan Mandalika, 2022)
This study aims to determine the percentage of errors produced by students according to Kastolan theory, the error's location, and the factors contributing to those errors when doing Mathematic. The study used the descriptive qualitative method. Based on the Kastolan theory, this study attempts to describe student errors in resolving mathematical problems. In this study, the instrument is a written test. The results showed that the conceptual error in question 1 was 71%, the procedural error was 67%, and the technical error was 65%. In question 2, there are 69% conceptual errors, 55% procedural errors, and 48% technical errors. While the conceptual error is 63%, the procedural error is 57%, and the technical error is 47% in question number 3. As a result, it showed that students' most common errors are conceptual. Students make mistakes when solving problems in the Two-variable Linear Equation System for a variety of reasons, including 1) lack of understanding of the questions given, leading to confusion in solving problems; 2) lack of caution in calculations, leading to incorrect results; 3) lack of ability to change the form of the problem into a mathematical model, and 4) lack of knowledge of the steps in solving the problem.